2008
DOI: 10.1111/j.1460-9568.2008.06302.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of CB1 and D2 receptors in rats: predominant role of CB1 in the increase of alcohol relapse

Abstract: The classical dopamine D2 receptor has been widely studied in alcoholism. Recently, different studies have explored the role of the CB1 receptor in alcohol-related behavior. In alcohol addiction, relapse is one of the central features. In light of this, we investigated the functional roles of and interactions between CB1 and D2 receptors in alcohol relapse. We used the learned task of alcohol operant self-administration in Wistar rats. In order to evaluate alcohol relapse, we set up a protocol essentially base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In our experimental model this downregulation occurs in the absence of DRD2, which suggests that the dopaminergic system affects the interaction between ethanol and the endocannabinoid system. Similarly, Alen et al (2008) showed that pharmacological inactivation of DRD2 prevents cannabinoid-induced alcohol relapse. These results are in agreement with the hypothesis that DRD2-mediated neurotransmission is critical for ethanol-related neuronal signaling and suggest that a functional interaction between ethanol and the dopaminergic and endocannabinoid systems exists in the mammalian brain.…”
Section: Discussionmentioning
confidence: 97%
“…In our experimental model this downregulation occurs in the absence of DRD2, which suggests that the dopaminergic system affects the interaction between ethanol and the endocannabinoid system. Similarly, Alen et al (2008) showed that pharmacological inactivation of DRD2 prevents cannabinoid-induced alcohol relapse. These results are in agreement with the hypothesis that DRD2-mediated neurotransmission is critical for ethanol-related neuronal signaling and suggest that a functional interaction between ethanol and the dopaminergic and endocannabinoid systems exists in the mammalian brain.…”
Section: Discussionmentioning
confidence: 97%
“…Remarkably, some of the behavioural features of orally self-administered ACD are sensitive to the pharmacological modulation of the cannabinoid CB1 receptor [17], as well as of the opioid neurotransmission [42]. These systems are largely involved in the induction of alcohol drinking behaviour and relapse [59], [60], [35] and can likely influence ACD drinking behaviour through the modulation of the DAergic reward pathway, thus causing DA release in the nucleus accumbens [61].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the recent increase in the literature regarding CB1 receptors as a pharmacological target for the treatment of alcoholism, there have been several extensive reviews published [209][210][211]. Based on these studies and recent findings from our own group [212], it is plausible to conclude that the endocannabinoid system mediates not only alcohol intake but the motivational and emotional properties of alcohol intake, seeking and craving.…”
Section: B) Pharmacological Manipulations Of the Endogenous Cannabinomentioning
confidence: 94%